THE HISTORY OF LANGUAGE IS THE HISTORY OF THE NATION - Gurbangul Myradova (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
The history of the language is closely connected with the history of the people, more precisely, it is an integral part of the nation’s history. Abysetdar Kazy’s “Jengnama” poem contains valuable information not only about the history of the Turkmen people and its cultural heritage but also about the history of the Turkmen language. In “Jengnama,” imperative, conditional, and optative verb forms are widely used. Although the grammatical structures forming these verb types are largely similar to those in modern Turkmen, certain formal peculiarities are present. These features emerge because Abdysetdar Kazy employed the traditional Central Asian Turkic literary language alongside Turkmen linguistic units of that period. For instance, the poem features forms such as -sa idi / -se idi or -saýdy / -seýdi, in addition to the -sady / -sedi optative forms found in modern Turkmen. Regarding the particles used with the imperative mood, some are still present in the modern Turkmen language (e.g., -gyn / -gin), while others are found exclusively in the language of the poem (e.g., -gyl / -gil). This provides clear evidence that Abdysetdar Kazy’s “Jengnama” was composed in the Central Asian Turkic literary language.